2020
DOI: 10.5194/acp-20-15725-2020
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn about urban air quality with regard to the first outbreak of the COVID-19 pandemic? A case study from central Europe

Abstract: Abstract. Motor vehicle road traffic in central Budapest was reduced by approximately 50 % of its ordinary level for several weeks as a consequence of various limitation measures introduced to mitigate the first outbreak of the COVID-19 pandemic in 2020. The situation was utilised to assess the real potentials of urban traffic on air quality. Concentrations of NO, NO2, CO, O3, SO2 and particulate matter (PM) mass, which are ordinarily monitored in cities for air quality considerations, aerosol particle number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
(50 reference statements)
5
36
0
Order By: Relevance
“…the previous paragraph). All this is in accordance with the conclusions of our more extensive study dedicated to this issue (Salma et al, 2020b).…”
Section: Concentrations and Their Ratiossupporting
confidence: 92%
See 3 more Smart Citations
“…the previous paragraph). All this is in accordance with the conclusions of our more extensive study dedicated to this issue (Salma et al, 2020b).…”
Section: Concentrations and Their Ratiossupporting
confidence: 92%
“…The dependency also pointed to the size-dependent chemical composition, which is typical for urban particles. All this is in line with the ideas on the major source types such as vehicle emissions, biomass burning or new particle formation and diameter growth (NPF) events (Salma et al, 2014(Salma et al, , 2017(Salma et al, , 2020a(Salma et al, , 2020b and the particle number size distributions in Budapest (Salma et al, 2011). Photochemical processing may also play a role through chemical ageing (Furutani et al, 2008).…”
Section: Effective Critical Dry Particle Diameterssupporting
confidence: 66%
See 2 more Smart Citations
“…Meanwhile, a general increase in ozone levels has also become evident, attributable to the "weekend effect", or, in this case, the more pronounced "lockdown effect" of NO x -O 3 chemistry [4,5]. After the first wave of the pandemic, air pollution reduction has been reported from numerous locations worldwide [6][7][8][9][10][11], and air quality was soon identified as a mediating factor between mobility reduction and COVID cases [12][13][14]. However, systematic investigation of global measurements revealed that the air quality improvement was not necessarily observable for every location in their respective lockdown period, and, notably, the Central-Eastern European region suffered a major increase in PM 2.5 concentrations during the lockdown [8].…”
Section: Introductionmentioning
confidence: 99%